Essays on Education and Performance Pay - (:unkn) unknown (My University, 2024)
The first chapter of this work examines the returns to education for workers who pursue additional education after time out of the labor force. It compares those who remain in the labor force during additional education and those who drop out of the labor force during additional education. It compares two cohorts of the NLSY, utilizing a difference equation to estimate the returns to education for workers who pursue additional education after time spent out of school and in the labor force. The results indicate a sheepskin return of approximately 14% for those who remain in the labor force and a return of approximately 9% to years of additional education for those who drop out of the labor force. This contrasting pattern of returns is robust to sample selection correction and a variety of checks. This points to key differences between the internal labor market faced by those remaining in the labor force and the external labor market faced by those dropping out of the labor force. A policy focused on re-training workers should account for these differences. This is the first work to compare workers who pursue additional education while remaining in the labor force to workers who pursue additional education and drop out of the labor force. However, it does not fully account for all threats to causation. Further research could pursue these and make use of data with more clearly defined periods of education. The second chapter of this work examines the influence of locus of control on sorting into performance pay jobs. It uniquely examines different types of performance pay schemes, demonstrating sharp differences between them. Bivariate probit estimates indicate workers with an internal locus of control sort into individual schemes but not joint schemes. Wage equations reveal that adding locus of control modestly reduces the return to individual performance pay but that in more complete specifications, the return to an internal locus of control itself becomes vanishingly small, which suggests that its primary importance is in sorting (not only into performance pay but into education and occupation). The third chapter of this work examines the influence of receiving performance pay on the probability that a worker will divorce. Uniquely, it compares two different cohorts of the National Longitudinal Survey of Youth. Probit estimates show that, for men, receiving performance pay has no impact on the probability of divorce in the older cohort and possibly decreases the probability of divorce in the younger cohort. For women, receiving performance pay increases the probability of divorce in the older cohort and has no impact in the younger cohort. This pattern persists even when conditioning on earnings and hours worked.
Keywords: divorce; locus of control; performance pay; returns to education; sheepskin effects; working in school